RADON INFILTRATION BUILDING ENVELOPE TEST SYSTEM: EVALUATION OF BARRIER MATERIALS. Issue 1 (23rd August 2021) - Gaskin, Janet; Li, Yunyi Ethan; Ganapathy, Gnanamurugan; Nong, Gang; Whyte, Jeffrey; Zhou, Liang Grace
Abstract: The performance of radon barrier materials currently available for housing foundations was evaluated using a unique radon infiltration building envelope test system that was designed to test radon prevention and mitigation systems using real world construction techniques. The reduction in radon concentration measured across the air barrier in the foundations has been used to evaluate five representative barrier materials installed in the radon infiltration building envelope test facility. The reduction in radon concentration in the mock house varied from 68% for 6 mil polyethylene to 98% for the spray polyurethane foam. The five representative barrier materials were selected after determining the radon diffusion coefficient and the corresponding radon resistance from samples of 14 barrier materials in a radon diffusion testing chamber. The Canadian experience evaluating whether radon barrier materials would satisfy building code requirements was described.